Eco-Epidemiology and Microbiological Evaluation of Poultry Salmonellosis in North Central Nigeria, and its Socioeconomics and Public Health Impacts - Fasina, Folorunso Oludayo (University of Pretoria, 2024)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2024.